MODELING OF DISCRETE CELL NEURAL NETWORKS - Nesterenko, B. B.; Novotarsky, M. A. (Radio Electronics, Computer Science, Control, 2024)
In the paper the substantiation of availability of application discrete cellular neural networks for solving of boundary value problems of mathematical physics by local – asynchronous methods is given. Basic elements of APROnets are shortly described and the discrete cellular network submitted as a two-level APRO-net is offered. Base principles of functioning of the given network which determine evolution of consecutive steps are considered. The technique of formation of real working loading and the basic approaches to training is described.